The Dynamics of Religious Conflict in Indonesia: Contestation and Resolution of Religious Conflicts in The New Order Age (Al-Adyan: Journal of Religious Studies, 2021)
Social conflicts in Indonesia are often associated with political turmoil and disappointment with the hegemony of power.  Therefore, it is important to understand comprehensively how the dynamics of religious conflict in Indonesia, especially during the New Order era.  As we know that this research is a literature study to understand the contestation of religious conflicts and how conflict resolution was implemented by the government in resolving ethnic-religious conflicts during the New Order era.  Using qualitative methods, this study finds that there are several factors of ethnic and religious conflicts in Indonesia, especially during the New Order era, namely group identity conflicts, levels of chaos and social mobilization, repressive actions by power groups, and collective conflicts between communal groups.  This study also shows that for the resolution of social conflicts, the government uses a repressive and security approach to control the community, and there is also a cultural approach from civil society as a form of resistance for the government.  Civil society also plays an active role in promoting peace agreements between conflicting groups.Konflik sosial di Indonesia seringkali dikaitkan dengan kekacauan politik dan kekecewaan terhadap hegemoni kekuasaan. Karena itu, penting untuk memahami lebih komprehensif bagaimana dinamika konflik agama di Indonesia, khususnya pada masa Orde Baru. Sebagaimana kita ketahui bahwa. Penelitian ini merupakan studi kepustakaan untuk memahami kontestasi konflik agama dan bagaimana resolusi konflik yang diterapkan oleh pemerintah dalam penyelesaian konflik agama-etnis pada masa Orde Baru. Menggunakan metode kualitatif, penelitian ini menemukan bahwa ada beberapa faktor konflik etnis dan agama di Indonesia, khususnya pada masa Orde Baru, yaitu konflik identitas kelompok, tingkat kekacauan dan mobilisasi sosial, tindakan represif oleh kelompok kekuasaan, dan konflik kolektif diantara kelompok komunal. Penelitian ini juga menunjukkan bahwa untuk penyelesaian konflik sosial, pemerintah menggunakan pendekatan represif dan keamanan untuk mengontrol masyarakat, dan juga ada pendekatan budaya dari masyarakat sipil sebagai salah satu perlawanan bagi pemerintah. Masyarakat sipil juga berperan aktif dalam mendorong kesepakatan damai antara kelompok-kelompok yang berkonflik.